Concept and Implementation Strategies of Urban Planning Control in Metro Engineering Design - CHEN Zhenqiang (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] Rational urban planning control can effectively reduce the costs for metro project construction and operation, enhance the transport capacity and service quality of metro systems, and promote sustainable urban development. Therefore, it is essential to analyze and study urban planning control concepts and implementation strategies in metro engineering design. [Method] First, the importance of urban planning control in metro engineering design is analyzed, emphasizing its role in ensuring safe construction and operation, generating economic and social benefits, so as to meet environmental protection requirements. Then, six core concepts of urban planning control in metro engineering design and their theoretical foundations are explained. The application effectiveness of these concepts is demonstrated through relevant case studies in China and abroad. Next, Guangzhou Metro Line 11 is used as an example to verify the importance of urban planning control in metro engineering design, illustrating specific implementation methods in route planning, station layout, and operational models.Finally, representative metro projects in Beijing, Shanghai, and Guangzhou are selected to elaborate on key control points and implement strategies of urban planning when addressing project challenges such as environmental protection, route optimization, and land acquisition and demolition. [Result & Conclusion] Currently, shortcomings still exist in urban planning control in metro engineering design in China, while also facing new challenges and opportunities brought by the development of digital technologies. In the future, greater emphasis should be placed on the application of big data and artificial intelligence to enhance the accuracy and efficiency of urban planning control in metro engineering design.